2019
DOI: 10.1038/s41598-019-47445-5
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Crystallographic Structure and Oligomerization of Gloeobacter Rhodopsin

Abstract: Gloeobacter rhodopsin (GR) is a cyanobacterial proton pump which can be potentially applied to optogenetics. We solved the crystal structure of GR and found that it has overall similarity to the homologous proton pump from Salinibacter ruber , xanthorhodopsin (XR). We identified distinct structural characteristics of GR’s hydrogen bonding network in the transmembrane domain as well as the displacement of extracellular sides of the transmembrane helices relative to those of XR.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 65 publications
1
75
0
Order By: Relevance
“…In summary, it can be concluded that the CD spectrum of gR originated from the excitonic coupling between retinal chromophores located in a protein pentameric form (Fig. 8b) 15,33 . Due to change of temperature, the His87-Asp121 pair arrangement is altered leading to pentamer to monomer transition and the corresponding change of CD spectra at pH 5 and vanishing of CD exciton 9 .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In summary, it can be concluded that the CD spectrum of gR originated from the excitonic coupling between retinal chromophores located in a protein pentameric form (Fig. 8b) 15,33 . Due to change of temperature, the His87-Asp121 pair arrangement is altered leading to pentamer to monomer transition and the corresponding change of CD spectra at pH 5 and vanishing of CD exciton 9 .…”
Section: Discussionmentioning
confidence: 83%
“…The CD spectra of native gR as well as in the presence of different types of carotenoids were studied previously, and it was proposed that the CD of the gR-carotenoid complex is due to induced chirality of the carotenoid 10,11 . pH-dependent oligomer-monomer transition, and their CD spectra were reported by Demura et al 9 Recently it was reported that the pentameric form of the pigment predominant at pH 8 while the monomeric form at pH 3 15,33 . However, in presence of sal, the exact origin of the observed positive and negative CD lobes with the enhancement of intensity and reversal of the CD band sign compared to the native gR, is not clear.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The structure of N2098R was also compared with the cyanobacterial rhodopsin GR (PDB code 6NWD) 40 and ASR (PDB code 1XIO) 41 , which are included in the XLR and XeR rhodopsin clades, respectively. The overall structure of N2098R is similar to that of GR (RMSD 1.91 Å) and ASR (RMSD 1.40 Å) (Supporting Information Fig.…”
Section: Structure Of N2098r and Comparison With Those Of Br Gr Andmentioning
confidence: 99%
“…Unfortunately, several tissues located in the deepest zone cannot be investigated for clinical purposes. For this reason, researchers are studying alternative solutions, such as X-optogenetics, which involves X-rays, and U-optogenetics, which exploits sonoluminescence [51,52].…”
Section: Clinical and Tissue Engineering And Regenerative Medicine (Tmentioning
confidence: 99%